2021
DOI: 10.1097/cm9.0000000000001288
|View full text |Cite
|
Sign up to set email alerts
|

Role of various imbalances centered on alveolar epithelial cell/fibroblast apoptosis imbalance in the pathogenesis of idiopathic pulmonary fibrosis

Abstract: There have been recent extensive studies and rapid advancement on the pathogenesis underlying idiopathic pulmonary fibrosis (IPF), and intricate pathogenesis of IPF has been suggested. The purpose of this study was to clarify the logical relationship between these mechanisms. An extensive search was undertaken of the PubMed using the following keywords: “etiology,” “pathogenesis,” “alveolar epithelial cell (AEC),” “fibroblast,” “lymphocyte,” “macrophage,” “epigenomics,” “histone,” acetylation,” “methylation,” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 173 publications
0
20
0
3
Order By: Relevance
“…IPF also exhibits histological features of UIP/IPF pattern characterized by dense fibrosis causing architecture remodeling with frequent honeycombing, patchy lung involvement by fibrosis, subpleural and/or paraseptal distribution, fibroblast foci at the edge of dense scars (Spagnolo et al, 2018;Baratella et al, 2021). With extensive basic and clinical research on the pathogenesis of IPF in recent years, some potential therapeutic targets have been discovered (Wang et al, 2021). A large number of these targets are growth factors, cytokines, and their signaling pathways, including TGF-β, CTGF, IL-13, CCL-2, leukotriene receptor, lipid proinflammatory mediators, and their downstream signaling.…”
Section: Introductionmentioning
confidence: 99%
“…IPF also exhibits histological features of UIP/IPF pattern characterized by dense fibrosis causing architecture remodeling with frequent honeycombing, patchy lung involvement by fibrosis, subpleural and/or paraseptal distribution, fibroblast foci at the edge of dense scars (Spagnolo et al, 2018;Baratella et al, 2021). With extensive basic and clinical research on the pathogenesis of IPF in recent years, some potential therapeutic targets have been discovered (Wang et al, 2021). A large number of these targets are growth factors, cytokines, and their signaling pathways, including TGF-β, CTGF, IL-13, CCL-2, leukotriene receptor, lipid proinflammatory mediators, and their downstream signaling.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that apoptosis is increased in alveolar epithelial cells of patients with IPF but decreased in myofibroblasts, 27 with this imbalance contributing to IPF pathogenesis. 28 Furthermore, the use of therapies that can selectively manipulate apoptosis have been proposed. 29 Additionally, genetic variants within cell cycle genes have been shown to be associated with IPF development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Among the biological pathways that were significantly enriched for Cluster 2 were pathways related to apoptosis and cell cycle. It has been previously reported that apoptosis is increased in alveolar epithelial cells of IPF patients but decreased in myofibroblasts (23), with this imbalance contributing to IPF pathogenesis (24). Furthermore, the use of therapies that can selectively manipulate apoptosis have been proposed (25).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that apoptosis is increased in alveolar epithelial cells of IPF patients but decreased in myofibroblasts, 23 with this imbalance contributing to IPF pathogenesis. 24 Furthermore, the use of therapies that can selectively manipulate apoptosis have been proposed. 25 Additionally, genetic variants within cell cycle genes have been shown to be associated with IPF development and progression.…”
Section: Discussionmentioning
confidence: 99%